A intervenção do juiz nos contratos - Berland, Carla Turczyn (2007)
Contractual theory has undergone significant changes over the last years, mainly due to a shift from the liberal imprint of the 1916 Civil Code to a more socially-oriented perspective. This change, already noticeable in the 1988 Federal Constitution and in some statutes, such as the Consumer Code, grew more acute after the enactment of the 2002 Civil Code. Apart from incorporating the modern social contractual theory, using methods such as those of general clauses and indeterminate concepts, it gave judges more latitude to interfere in contracts. This thesis aims at examining aspects of modern contractual theory, as it appears in the Civil Code (expressed in a number of general provisions v.g. good faith; social function of contracts), as well as at analyzing the available forms for judicial intervention in contracts. It suggests that such judicial intervention is not only possible but even desirable mainly as a tool to prevent the contract from being unnecessarily terminated